What is the solution of this equation?
2(2x + 3) + 3x + 7 = 3(3x + 1)

Question

Asked 5/7/2014 10:30:11 AM

Updated 5/7/2014 10:45:42 AM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by debnjerry [5/7/2014 10:45:42 AM]

6x^2 + 4x + 9x + 6

6x^2 + 13x + 6

Question

Asked 5/7/2014 10:30:11 AM

Updated 5/7/2014 10:45:42 AM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by debnjerry [5/7/2014 10:45:42 AM]

Rating

3

2(2x + 3) + 3x + 7 = 3(3x + 1)

4x + 6 + 3x + 7 = 9x + 3

7x + 13 = 9x + 3

7x - 9x = 3 - 13

-2x = -10

x = -10 / -2

x = 5

4x + 6 + 3x + 7 = 9x + 3

7x + 13 = 9x + 3

7x - 9x = 3 - 13

-2x = -10

x = -10 / -2

x = 5

Added 5/7/2014 10:45:37 AM

This answer has been confirmed as correct and helpful.

29,947,606

questions answered

There are no comments.